Strategi Keuangan UMKM Dalam Mengatasi Perekonomian di Masa Pandemi Covid-19 di Kecamatan Baolan Kabupaten Tolitoli - Mardiana (Formosa Journal of Sustainable Research, 2022)
This study aims to determine the financial strategy of SMEs in overcoming the economy during the Covid-19 pandemic in Baolan District, Tolitoli Regency. The research informants were 12 informants, each of which consisted of 2 people representing six villages in the Baolan sub-district, Tolitoli Regency. The data analysis technique used is data reduction, data presentation and conclusion. The MSME financial strategy in dealing with the economy during the COVID-19 pandemic is still very simple, overall it only uses a simple budget, recording and control and does not report on business finances